Risk-factors and multimorbidity in oral anticoagulant-related intracerebral haemorrhage: a comparison of patients in pivotal trials and real life - Grundtvig, Josefine; Gaist, David; Christensen, Louisa; Ovesen, Christian; Havsteen, Inger; Iversen, Helle K; Christensen, Thomas; Lilja-Cyron, Alexander; Kruuse, Christina; Ægidius, Karen; Rosenbaum, Sverre; Meden, Per; et al. (Age & ageing, 2025)
We hypothesised that morbidity burden was higher in real-life patients with oral anticoagulant-related intracerebral haemorrhage (OAC-ICH) than direct oral anticoagulant (DOAC) trial-life patients (pivotal trial participants) and explored if pre-stroke morbidity was comparable (i) in real-life patients on DOAC or vitamin K antagonist (VKA) with ICH, and (ii) in trial-life patients versus real-life patients with OAC-ICH.The COOL-ICH cohort included 401 acute, consecutive patients with OAC-ICH (272 VKA-ICH, 129 DOAC-ICH) from the Capital Region of Denmark. Risk-factors and morbidity in trial-life patients were retrieved from publications.Risk-factors, CHADS2 and Charlson Comorbidity Index were comparable in DOAC vs VKA users in real-life. Pre-stroke modified Rankin Scale (mRS) was higher in DOAC users than in VKA users (median mRS 1 vs 0, P = 0.002). More DOAC users were women (53% vs 39%, P = 0.009). Compared to trial-life patients, age and proportion of women were higher in real-life patients. CHADS2-scores were comparable.In conclusion, burden of risk-factors and comorbidities were similar in real-life patients with DOAC-ICH and VKA-ICH, as well as in real-life patients compared to trial-life patients. However, real-life patients especially those on DOAC, were older and more frequently women than trial-life patients. It is reassuring that burden of comorbidity was similar in real-life and trial-life patients. Nevertheless, this report underlines the importance of recruiting adequate numbers of older people and women to cardio-vascular trials to ensure sufficient safety data to advice prescriptions in these very prevalent sub-groups of patients.
Veröffentlicht: 16. April 2025
Gesehen am 06.10.2025